2010
DOI: 10.1007/s10571-010-9565-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of SNAREs and Calcium Channels with the Borders of Cytoskeletal Cages Organizes the Secretory Machinery in Chromaffin Cells

Abstract: In chromaffin cells, SNARE proteins, forming the basic exocytotic machinery are present in membrane clusters of 500-600 nm in diameter. These microdomains containing both SNAP-25 and syntaxin-1 are dynamic and the expression of altered forms of SNAREs modifies not only their motion but also the mobility of the associated granules. It is also clear that SNARE microdomain location defines the place for individual vesicle fusion and that the alteration of cluster dynamics affects the fusion process itself. Intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Recent studies performed on neuroendocrine chromaffin cells reported the association of SNARE protein patches and clusters of voltage-gated Ca 2ϩ channels with the borders of cortical cytoskeletal cages (68,69). We show here the glucoseresponsive colocalization of Ca 2ϩ -responsive FAK (27) with ␤1 integrin and paxillin in patches at the basal ␤ cell membrane.…”
Section: Discussionsupporting
confidence: 54%
“…Recent studies performed on neuroendocrine chromaffin cells reported the association of SNARE protein patches and clusters of voltage-gated Ca 2ϩ channels with the borders of cortical cytoskeletal cages (68,69). We show here the glucoseresponsive colocalization of Ca 2ϩ -responsive FAK (27) with ␤1 integrin and paxillin in patches at the basal ␤ cell membrane.…”
Section: Discussionsupporting
confidence: 54%
“…Indeed the majority of SGs in the vicinity of the plasma membrane are tethered to the cortical actin network (6), and newly arriving vesicles are also caught in this dense mesh of F-actin (33). Other studies point to the existence of F-actin cages that organize the SNARE proteins SNAP25 and syntaxin-1 as well as L- and P/Q-type calcium channels, creating sites in the cortical actin network where SGs fuse preferentially (34). Consistent with these data, studies using total internal reflection fluorescence (TIRF) microscopy revealed that vesicle motion becomes restricted in the vicinity of the plasma membrane (35, 36).…”
Section: New Roles For Actin In Exocytosismentioning
confidence: 99%
“…Thus, the study of the secretory organization in neurite-alike structures in chromaffin cells appeared interesting to understand the fine-tuning of exocytosis when the endocrine organization evolves to a pseudoneuronal system. In addition to studying such organization, we use stochastic models of secretion (Gil et al 2000;Torregrosa-Hetland et al 2010Villanueva et al 2010) to study the influence of calcium channel accumulation and cytoskeletal organization in determining the kinetic differences in secretion found between neurite terminals and the cell body. Our study enriches the variety of roles assumed by the cortical cytoskeleton when governing the secretory process (Gutierrez 2012).…”
Section: Introductionmentioning
confidence: 99%